Effects of joint forest management on forest conditions in Khyber Pakhtunkhwa, Pakistan - Ahmed , Ayaz (Technium EcoGeoMarine, 2022)
This study measured the effects of joint forest management (JFM) on forest conditions in purposively selected three forest divisions of Khyber Pakhtunkhwa, Pakistan. The technique of experimental (JFM) versus control (non-JFM) group was applied. Assessment was made between JFM forest and nearby similar non-JFM forest located in the same forest-ecological and socio-economic settings. A total of 393 sample plots (234 from JFM forests while 159 from non-JFM forests) were assessed. Results of independent sample t-test revealed significant difference between JFM and non-JFM forests. Average tree density of JFM forests was 276 trees/ha while for non-JFM forests it was 247 trees/ha. Similarly average seedlings density/ha in JFM forests was 3114 as compared to 1987 in non-JFM forests. Data analysis explored that human disturbances were more in non-JFM forests as compared to JFM forests where joint forest management committees played active role in their protection. In JFM forests, forest protection and improvement activities were observed more times as compared to non-JFM forests. So, this can be concluded that JFM has remarkable contribution in protection and improvement of forests in study areas. It is recommended that network of JFMCs should be extended to non-JFM forests for protecting them from further degradation.